To shift the line given by the equation \( y = 3x + 2 \) one unit to the right and two units up, we can perform the following transformations:
-
Shift one unit to the right: To shift the graph of a function \( f(x) \) to the right, we replace \( x \) with \( (x - 1) \). For the equation \( y = 3x + 2 \), this gives us: \[ y = 3(x - 1) + 2 = 3x - 3 + 2 = 3x - 1 \]
-
Shift two units up: To shift the graph of a function up by \( c \) units, we add \( c \) to the entire function. In this case, we will add 2 to the equation we got from the first step: \[ y = (3x - 1) + 2 = 3x + 1 \]
Thus, the equation of the new line after the transformations is: \[ y = 3x + 1 \]
So the correct response is:
- y=3x+1